Development of biomimetic platforms to investigate the influence of the extra-cellular environment on immunological responses - Donaldson, Amy Rose (2017)
The immune system comprises highly sophisticated networks of cells and signalling molecules which function in concert to protect the body against pathogens. Within this system a role for the extra-cellular microenvironment as a crucial mediator of immune responses is becoming increasingly apparent.